ANALISIS PERENCANAAN PROGRAM CERIA BERNUMERASI DAN SATRIA SEBAGAI UPAYA PENGUATAN LITERASI DAN NUMERASI DI SEKOLAH DASAR - Eka Ulfa Khairani; Abraar Dzulqadri; M. Faisal; Rodiah (STKIP Subang, 2025)
This study aims to analyze the planning of the CERIA BERNUMERASI and SATRIA programs as efforts to strengthen literacy and numeracy in elementary schools. The research addresses the issue of students’ literacy and numeracy achievement, which remains at a moderate level based on Education Report data and National Assessment results. A descriptive qualitative approach was employed, with data collected through observations, document analysis, and discussions with teachers involved in program planning. The findings indicate that the program planning was developed systematically based on real school needs and included clearly defined objectives, target groups, learning materials, instructional methods, implementation schedules, and evaluation mechanisms. Literacy planning focused on meaningful reading, reading comprehension, and storytelling skills through read-aloud activities, discussions, and reflections, while numeracy planning emphasized basic mathematical concepts through game-based learning. Overall, the results show that the CERIA BERNUMERASI and SATRIA programs provide a structured and data-driven foundation for preparing the implementation of literacy and numeracy strengthening activities in elementary schools and have the potential to support the development of a sustainable literacy and numeracy culture.